Bone marrow‐derived mesenchymal stem cells microvesicles stabilize atherosclerotic plaques by inhibiting NLRP3‐mediated macrophage pyroptosis. (28th December 2020) - Lin, Yu; Liu, Meihan; Chen, Enqi; Jiang, Wei; Shi, Weidong; Wang, Zhiyuan
Abstract: Rupture of atherosclerotic plaques constitutes the major cause of thrombosis and acute ischemic coronary syndrome. Bone marrow‐derived mesenchymal stem cells microvesicles (BMSCs‐MVs) are reported to promote angiogenesis. This study investigated the role of BMSCs‐MVs in stabilizing atherosclerotic plaques. BMSCs‐MVs in mice were isolated and identified. The mouse model of atherosclerosis was established, and mice were injected with BMSCs‐MVs via the tail vein. The macrophage model with high glucose and oxidative damage was established and then incubated with BMSCs‐MVs. Nod‐like receptor protein 3 (NLRP3) expression, pyroptosis‐related proteins, and inflammatory factors were detected. Actinomycin D was used to inhibit the secretion of BMSCs‐MVs to verify the source of microRNA‐223 (miR‐223). The binding relationship between miR‐223 and NLRP3 was predicted and verified. BMSCs‐MVs with knockdown of miR‐223 were cocultured with bone marrow‐derived macrophages with knockdown of NLRP3, and then levels of miR‐223, NLRP3, pyroptosis‐related proteins, and inflammatory factors were detected. BMSCs‐MVs could reduce the vulnerability index of atherosclerotic plaques and intima‐media thickness in mice, and inhibit pyroptosis and inflammation. BMSCs‐MVs inhibited pyroptosis and inflammatory factors in macrophages. BMSCs‐MVs carried miR‐223 to inhibit NLRP3 expression and reduce macrophage pyroptosis, thereby stabilizing the atherosclerotic plaques.